STRATEGI PENGEMBANGAN PRASARANA DAN SARANA OBJEK WISATA CANDI PADANG ROCO KABUPATEN DHARMASRAYA - Alvionita, Rediana; Silfeni, Silfeni; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2016)
This research was motivated by the lack of infrastructure and facilities in the tourism site Candi Padang Roco. The purpose of research is to determine the development strategy of infrastructure and facilities of tourism site Candi Padang Roco.This research is a descriptive study with qualitative data. Data was collected using interviews, observation and documentation involving informants with snowball sampling technique, namely: four managers (Department of Tourism), three people Kenagarian Siguntur and three travelers. Data analysis techniques in the study include: data reduction, data presentation and conclusions.The results of this study stated that: 1) The strength of the infrastructure and facilities of tourism site Candi Padang Roco, has been the availability of infrastructure and facilities most tourism site. 2) The weakness of infrastructure and facilities of tourism site are the road conditions are not good, there is no electricity, clean water is not available, there is no public transport to tourism site there is no shop, cafÃ© or restaurant and not a home stay. 3) Opportunities that have the infrastructure and facilities to complement the tourism site is their discourse managers for the development of infrastructure and facilities of tourism site like building a bridge. 4) Threats to infrastructure and facilities of tourism site is the presence of the other attractions that are superior, lack of awareness of travelers to keep the tourism siteDevelopment strategy of infrastructure and facilities for tourism site Candi Padang Roco are improv road infrastructure. Using the river as a source of clean water and lighting. Provide nurses and first aid required by tourists. Provide homestay which have unique characteristics. Build a restaurant or cafÃ©. Provide rental bikes as transportation to tourism site. Conducting conduct training to the community and invite the community to participate actively in creating tourist charms, tourism attraction at least once a week.Key words: Development Strategy, Infrastructure and Facilities of tourism site